Application of the reaction engineering approach (REA) for modeling of the convective drying of onion. Issue 4 (12th March 2017) - Compaore, A.; Dissa, A. O.; Rogaume, Yann; Putranto, Aditya; Chen, Xiao Dong; Mangindaan, Dave; Zoulalian, André; Rémond, Romain; Tiendrebeogo, E.
ABSTRACT: In this study, the drying of thin layers of the "Violet de Galmi" onion (a variety mainly grown in West Africa) is presented in this article, along with the reaction engineering approach (REA) modeling for a comprehensive understanding of the drying kinetics. The experiments were conducted on a lab-scale dryer to form thin layer of cylindrical onion slice. By performing this experiment, the standard activation energy is evaluated and modeled. The model is validated by simulating the drying rates under various drying conditions. The comparison of simulation and experimental data is found to be satisfactory. This approach allows the determination of the internal characteristics of the onion for the further studies such as design of solar dryer for onion.